PERBEDAAN ROW TERHADAP PERFORMAN AYAM PETELUR GROWER DALAM KANDANG CLOSED HOUSE - Sri, elvin (Universitas Islam Balitar, 2024)
This study aims to evaluate the impact of row differences on the productivity of Isa Brown laying hens during the grower phase, with a focus on body weight gain and uniformity. The research was conducted at Slorok Farm, Blitar Regency using a close house system. A total of 192 laying hens were placed in each row 1 and row 2 which had been determined in a closed cage. Weight gain and uniformity were measured weekly from 7 to 10 weeks of age. The results were analyzed using the unpaired T test to determine significant differences between the two levels. The results of the research showed that there was no real difference in body weight gain and uniformity between Row 1 and Row 2, this shows that the placement of the Row does not affect the productivity of Isa Brown laying hens in the grower phase with a closed cage system. Keywords: Isa Brown laying hens, performance, different rows, grower phase, closed cage.